Zero-current Zero-voltage Transition Pwm Converters With Magnetically Coupled Auxiliary Circuit - Martins, Mário L. da S.; Russi, Jumar L.; Pinheiro, José R.; Hey, Hélio L. (Eletrônica de Potência, 2008)
This paper presents a novel methodology to synthesize Zero-Current Zero-Voltage Transition (ZCZVT) topologies. The proposed methodology is based on the Auxiliary Voltage Source (AVS) concept, which permits extend the proposed new circuits to an entire class of converters. As the AVS concept is derived directly from the Resonant Transition mechanism, the new class of ZCZVT converters resembles some of the well-known Zero-Voltage Transition (ZVT) converters, holding their main advantages such as simplicity, low reactive energy and high performance. Theoretical and experimental analyses are carried out throughout the paper taking the boost converter as the case study. Nevertheless, it can be extended to other PWM topologies, even the AC-DC and DC-AC converters. Experimental and comparative results have been obtained from three laboratory prototypes rated to 1 kW, 50 kHz, confirming the feasibility of the novel synthesis concept and also the reliability of the new ZCZVT converters in what refers to efficiency as well as to di/dt and dv/dt control.